Probabilistic analysis of the active earth pressure on retaining wall for c-f soil backfill under seismic loading conditions (2017)
This paper describes a methodology based on the Rosenblueth point estimate method to analyze the active earth pressure developed on retaining walls for c-f soil backfill under seismic loading conditions. The fundamentals of this methodology are to use two point estimates to examine a variable in the safety analysis: the mean value and the standard deviation. When the horizontal seismic acceleration coefficient increases, the overturning factor of safety decreases, whereas the probability of failure increases, particularly for coefficients greater than 0.2. In addition, the mean factor of safety increases when the vertical seismic acceleration coefficient increases, but the probability of failure remains practically identical for the considered critical factor of safety (1.15).